STUDI LITERATUR: PENILAIAN PEMBELAJARAN MATEMATIKA YANG MENDUKUNG KEMAMPUAN BERPIKIR KREATIF - Sumardi W Ndolu; Andrian Runtius Lalang (Journal of Character and ELementary Education, 2023)
This literature study aims to examine and describe the assessment of mathematics learning that supports creative thinking skills. Based on the literature study conducted, it was found that learning mathematics provides opportunities for students to think creatively in terms of solving mathematical problems that require strategies or solutions that are diverse and different, as well as unique and new. This can be done through problem-solving and the submission of mathematical problems by students through an open assessment instrument. The assessment results aim to provide constructive feedback to teachers and students so that the quality of learning can be improved. Therefore, assessment instruments in mathematics learning need to be developed appropriately and correctly and integrate problem-solving and mathematical problem-posing that provide opportunities for students to solve them in various ways, so as to provide feedback for teachers to improve students' creative thinking skills.